Association between secondhand smoke exposure and hypertension in never smokers: a cross-sectional survey using data from Korean National Health and Nutritional Examination Survey V, 2010–2012 - Young Sik Park; Chang-Hoon Lee; Sang Haak Lee; Kwang-Ha Yoo; Yu-Il Kim; Chul Min Ahn; Ju Ock Kim; Ju-Heon Park; Jae Yeol Kim; Eun Mi Chun; Tae-Hoon Jung (BMJ Open)
Objectives Secondhand smoke (SHS) exposure is associated with cardiovascular disease. This study aims to determine the association between SHS exposure estimated by questionnaire and hypertension in Korean never smokers.Setting Korean National Health and Nutrition Examination Survey (KNHANES) V was conducted from 2010 to 2012.Participants We selected the never smokers aged over 20 years who answered the question about the SHS exposure.Primary and secondary measures SHS exposure in both the home and work place was estimated using a self-reporting questionnaire. We investigated the association between SHS exposure and hypertension by using multivariate analysis. And we evaluated the mean systolic and diastolic blood pressure values according to SHS exposure after adjusting for possible confounding factors. All analyses were stratified by women and men.Results There were 10 532 (women 8987 and men 1545) never smokers. We divided the subjects into three groups according to the amount of SHS exposure: none—group I, <2 hour/day—group II and ≥2 hour/day—group III. Using multivariate analysis, hypertension was more commonly associated with group III than group I in women (adjusted OR 1.50, 95% CI 1.00 to 2.04, p=0.011). Adjusted mean systolic and diastolic blood pressure values in women who were not taking antihypertensive medication were significantly elevated in group III by 2.3 and 1.7 mm Hg, respectively.Conclusion SHS exposure is significantly associated with hypertension in women never smokers.